2019
DOI: 10.1038/s41598-019-42579-y
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Diagnosis of Hematologic Diseases in Magnetic Resonance Imaging of Lumbar Spines

Abstract: We aimed to assess feasibility of a support vector machine (SVM) texture classifier to discriminate pathologic infiltration patterns from the normal bone marrows in MRI. This retrospective study included 467 cases, which were split into a training (n = 360) and a test set (n = 107). A sagittal T1-weighted lumbar spinal MR image was normalized by an intervertebral disk, and bone marrows were segmented. The various kernel functions and SVM input dimensions were experimented to construct the most optimal classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It showed the Random Forest as the best model for prediction with measurements (accuracy: 83.1%; specificity 89.5%; positive predictive value: 88.0% and AUC: 90.2%). One slightly different retrospective study 34 in the field of medical imaging with 467 cases (training set: 360 and test set: 107) constructed SVM texture classifier model to see the feasibility of differentiating bone marrow with hematologic diseases. With the above-mentioned training set, the values of accuracy, sensitivity and specificity and AUC were 82.8%, 81.7%, 83.9% and 0.895 (p < 0.001) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It showed the Random Forest as the best model for prediction with measurements (accuracy: 83.1%; specificity 89.5%; positive predictive value: 88.0% and AUC: 90.2%). One slightly different retrospective study 34 in the field of medical imaging with 467 cases (training set: 360 and test set: 107) constructed SVM texture classifier model to see the feasibility of differentiating bone marrow with hematologic diseases. With the above-mentioned training set, the values of accuracy, sensitivity and specificity and AUC were 82.8%, 81.7%, 83.9% and 0.895 (p < 0.001) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The same images were used to detect osteoporosis, but the highest AUC was only 0.810 [7]. Our predictive performance was also higher than the recent study of discriminating diseased bone marrows with a support vector machine texture classifier, which gave the AUC of 0.895 [20] and another study of differentiating bone marrow metastatic diseases with the highest AUC of 0.912 [9]. Building a radiomics model involved various steps of postprocessing, feature selection and applying an appropriate classifier.…”
Section: Discussionmentioning
confidence: 84%
“…ML has been proposed for various applications in the context of spine imaging [39]. Promising results have been reported for the differential diagnosis of bone marrow infiltration and normal signal patterns in hematologic diseases [40]. Similarly, initial investigations have shown that radiomic signatures could help in the prediction of metastasis appearance in vertebral bodies [41].…”
Section: Discussionmentioning
confidence: 99%